Factors Affecting Participation of Children with Cerebral Palsy in Meaningful Activities: Systematic Review. Issue 4 (1st October 2021) - Pashmdarfard, Marzieh; Richards, Lorie Gage; Amini, Malek
Abstract: This is a systematic review using PRISMA guidelines to review the factors affecting participation of children with cerebral palsy (CP), the most common childhood motor disability. Inclusion criteria consisted of publications in a peer-reviewed journal between 2000 and 2018, and at I, II, III, and IV levels of AOTA Evidence. After the title, abstract, and a full text screening, 31 articles met eligibility to be included. The studies examined ADLs (12), IADLs (9), play and leisure (19), and social participation (14), but only 3 in rest/sleep, 1 in work, and 8 in education. Gross motor and manual function, CP type, home, and community physical environment, were the most common factors affecting individuals' participation with CP. Results imply occupational therapists must evaluate clients on all factors shown to facilitate or inhibit participation to ensure an adequate intervention plan. However, evaluating every individual case in the occupational therapy process is time-consuming and difficult. Based on this study's findings, we suggest occupational therapists prioritize evaluating motor skills (gross and fine), the most influential of the factors in all areas of participation. Occupational therapists also could advocate for policy around community environmental barrier removal.